2022
DOI: 10.1088/1742-6596/2377/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on seismicity declustering methods and completeness magnitude in eastern Sunda Arc

Abstract: Data declustering separates mainshocks from both foreshocks and aftershocks while a reliable estimate of completeness magnitude is a key point in seismic parameter determination. These play a role in seismicity-related work. In this preliminary study, we reported seismicity in two Indonesian provinces, namely NTB and NTT, as part of eastern Sunda Arc using the USGS catalogue during 1970-2021 based on performance of three declustering methods (Gardner and Knopoff, Reasenberg, Uhrhammer). These methods were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the last year's study [32], the group worked with an alumnus from Physics Study Program, exploring the best appropriate technique suitable for characterising seismicity through determination of a reliable declustering process and completeness magnitude for eastern Indonesian provinces, including West Nusa Tenggara (NTB) and East Nusa Tenggara (NTT). The final results revealed that the Reasenberg and Best Combination (BC) techniques were both reliable for accurate calculations of magnitude of completeness Mc and the other two seismic parameters, namely a and b.…”
Section: Projects Towards Seismological and Volcanological Topicsmentioning
confidence: 99%
“…In the last year's study [32], the group worked with an alumnus from Physics Study Program, exploring the best appropriate technique suitable for characterising seismicity through determination of a reliable declustering process and completeness magnitude for eastern Indonesian provinces, including West Nusa Tenggara (NTB) and East Nusa Tenggara (NTT). The final results revealed that the Reasenberg and Best Combination (BC) techniques were both reliable for accurate calculations of magnitude of completeness Mc and the other two seismic parameters, namely a and b.…”
Section: Projects Towards Seismological and Volcanological Topicsmentioning
confidence: 99%